If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3y = -40 Solving 4x + 3y = -40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 4x + 3y + -3y = -40 + -3y Combine like terms: 3y + -3y = 0 4x + 0 = -40 + -3y 4x = -40 + -3y Divide each side by '4'. x = -10 + -0.75y Simplifying x = -10 + -0.75y
| 5x^2+3x-14=0 | | 4s^2+33s+54=0 | | 50=6(k+8)-5 | | (9x-4)(8x+5)= | | a(n)=-14+(n-1)(2) | | 3n+7(1+2n)=24 | | X-3y-8=0 | | 9x-7=17x-2 | | 12=p-2(6p+5) | | x^3-3x^2-6x=20 | | p^2-7p+6= | | -x^2-18=x^2+12x | | -(3+8x)=-51 | | 5x+40=9x-24 | | 4y=456-2x | | a-10=-3 | | 10x^2-4=6x^2+5 | | 3+4=14 | | 3(2n+8)=-18 | | x-4+8x=6x-16 | | y^2-4y+4= | | 2m^2=21m | | -5x^2+16x-3=0 | | 4x^3-27x^2-11x-1=0 | | 4x^2-49= | | -x^2-12x+5=0 | | y=1-x-x^2 | | 3x^2+3x+11=0 | | 35q=-5 | | 3x^2+12x+27=0 | | 65=-4-3(1+3r) | | w/4-4=3 |